The degree of extra-pair paternity increases with genetic variability - Petrie, Marion (The National Academy of Sciences, 1998)
The amount of extra-pair paternity in socially monogamous bird species varies from 0% to 76% extra-pair offspring. The causes of this remarkable interspecific variation are largely unknown, although intraspecific analyses suggest that females seek extra-pair matings to improve the genetic quality of their offspring. If this is a general explanation for the occurrence of extra-pair matings, then proportionally more females should seek to modify the paternity of their clutch when there is more variation among males in their genetic quality. Here we test this prediction in birds and show that interspecific variation in the proportion of extra-pair offspring is positively related to the proportion of polymorphic loci as measured by protein electrophoresis, even when controlling for potentially confounding variables. Genetic variability was also assessed, for sister pairs of species and populations differing significantly in extra-pair paternity, by using random priming, which provides an estimate of genome-wide diversity. We found that genetic diversity was higher in the populations with a higher level of extra-pair paternity. These results suggest that the amount of genetic variability in a population may be an important factor influencing mating patterns.